2016
DOI: 10.1016/j.cherd.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of future electric and hybrid vehicles: A cradle-to-grave systems engineering approach

Abstract: Electric mobility is playing an important and growing role in the context of sustainable transport sector development. This study presents the life cycle assessment of an electric car based on the technology of Lithium-ion battery (BEV) for Europe and compares it to an internal combustion engine vehicle (ICEV). According to a cradle-to-grave approach, manufacturing, use and disposal phases of both vehicles have been included in the assessment in order to identify the hot spots of the entire life cycles. For el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 21 publications
1
60
1
Order By: Relevance
“…The selected functional unit was 1 km driven by a medium-sized passenger car characterized by a lifespan of 150,000 km. Life lengths of vehicles can vary largely according to the specific characteristics of different models, but the assumed lifespan value is widely used as a reference for LCA studies of small-to medium-sized passenger cars [4,14,18,19,22]. A detailed description of the modeling assumptions for each life cycle stage is given in the following sections.…”
Section: Life Cycle Assessment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The selected functional unit was 1 km driven by a medium-sized passenger car characterized by a lifespan of 150,000 km. Life lengths of vehicles can vary largely according to the specific characteristics of different models, but the assumed lifespan value is widely used as a reference for LCA studies of small-to medium-sized passenger cars [4,14,18,19,22]. A detailed description of the modeling assumptions for each life cycle stage is given in the following sections.…”
Section: Life Cycle Assessment Analysismentioning
confidence: 99%
“…Moreover, the impact reduction potential of EVs is estimated as gradually increasing with the optimization of the electricity mix (renewable energies penetration) and the wide application of advanced electricity technologies [18][19][20][21]. The disposal phase was found to have a minor influence on the total environmental burdens [22], even if different recycling technologies for the end-of-life of the vehicle could significantly differ in terms of impact [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, EVs present cradle-to-grave environmental impacts, especially due to the use of lithium batteries. The manufacturing phase corresponds to the highest environmental burden of EVs, mainly in the toxicity categories because of the use of metals in the battery pack [4]. To address these issues, it is crucial to minimize power losses in the battery and develop proper recycling tools [5].…”
Section: Introductionmentioning
confidence: 99%
“…The expected population rise will unavoidably result in an increase of energy demand and vehicle use. Light-duty vehicles are predicted to increase significantly by 2050, which implies a strong increase in fuel consumption and pollution related to the transport sector (Tagliaferri et al, 2016). Alternative fuels and technologies to decrease the generated greenhouse gas emissions in the energy and transport sectors are widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel-cell cars use hydrogen to generate electricity. It has been shown that heavy metals in battery manufacturing and other aspects of the battery lifecycle increase the environmental impact of this type of cars (Tagliaferri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%